Suppression of annual grass weeds by AR542 endophyte infection in dryland tall fescue pastures - Tozer, K.N.; Lucas, R.J.; Edwards, G.R. (New Zealand Plant Protection, 2007)
The effect of endophyte infection of tall fescue (with and without AR542 endophyte Neotyphodium coenophialum) plant competition (white versus Caucasian clover with and without subterranean clover overdrilled) and spring stocking rate (10 versus 20 ewes/ha) on the population size of annual grass weeds was monitored in a pasture on dry stony soils in Canterbury Barley grass (Critesion murinum) cover and seedhead production were lower in AR542 than endophyte free pastures and where subterranean clover was overdrilled than where it was not Vulpia hair grass (Vulpia spp) seedhead production and cover were lower where subterranean clover was overdrilled and where Caucasian rather than white clover was sown Ewe stocking rate did not affect annual grass weed cover or seedhead density The results indicate that sowing tall fescue with AR542 endophyte may be a useful management tool to enhance growth of the perennial grass and reduce invasion of barley grass into dryland pastures